Prediction of health impact of nitrogen dioxide air pollutant from petrochemical industry on communities in Kemaman and Dungun, Malaysia - Ibrahim, Mohd Habir (2012)
Petrochemical industry is one of the major air pollutant generators around the world. The same scenario is observed occurring at North East of Peninsular Malaysia where this industry is estimated of producing more than half of the Malaysian petrochemicals products. This research will focus on the point source NO2 emission emitted by the petrochemicals plants. The ISCT3 air dispersion of Gaussain Transport Model is used to simulate the average predicted on ground concentration of NO2 emitted by point source from the petrochemicals plants. The simulation covers major input of geographical domain set up, NO2 generators specification and meteorological parameters. The geographical domain set up is at 20 km x 20 km covering area centre of the petrochemicals plants with 0.5 km receptors grid spacing. The NO2 emission rate was estimated through the use of the actual sampling data and the ultimate fuel analysis method. The NO2 generated combined with five yearly (2004-2008) meteorological data was applied to perform the simulation at the optimum correlation of wind direction at the range of -29o to 45o angle which leads to the polynomial model of predicting the wind direction. The simulation performed discovered that the maximum predicted of monthly and yearly average on ground NO2 concentration to receptors range from 8.42 to 17.51 ug/m3 and from 4.96 to 6.90 ug/m3 respectively. The yearly predicted average concentration shows that the value is below the WHO and Malaysian DOE guideline which is at 40 and 90 ug/m3 respectively. This average maximum yearly predicted NO2 indicate that the Hazard Index value is less than 1.00 which conclude that the is no appreciable harmful effects to receptors surrounding the petrochemicals industry. Benchmarking of Hazard Index could not be performed at the predicted monthly average since there is no available standard guideline.